The Sonodynamic Effect of Curcumin on THP-1 Cell-Derived Macrophages. (30th December 2012) - Wang, Fengping; Gao, Qianping; Guo, Shuyuan; Cheng, Jiali; Sun, Xin; Li, Qiannan; Wang, Tengyu; Zhang, Zhiguo; Cao, Wenwu; Tian, Ye
Abstract : Curcumin is extracted from the rhizomes of the traditional Chinese herb Curcuma longa and has been proposed to function as a photosensitizer. The potential use of curcumin as a sonosensitizer for sonodynamic therapy (SDT) requires further exploration. This study investigated the sonodynamic effect of curcumin on macrophages, the pivotal inflammatory cells in atherosclerotic plaque. THP-1-derived macrophages were incubated with curcumin at a concentration of 40.7  μ mol/L for 2 h and then exposed to pulse ultrasound irradiation (2 W/cm 2 with 0.86 MHz) for 5–15 min. Six hours later, cell viability was decreased in cells that had been treated with ultrasound for 10 and 15 min. After ultrasound irradiation for 15 min, the ratio of apoptotic and necrotic cells in SDT group was higher than that in ultrasound group, and the ratio of apoptotic cells was higher than that of necrotic cells. Both loss of mitochondrial membrane potential and morphological changes of cytoskeleton were apparent 2 h after treatment with curcumin SDT. These findings support that curcumin had sonodynamic effect on THP-1-derived macrophages and that curcumin SDT could be a promising treatment for atherosclerosis.